Optimization of tapioca starch-modified natural rubber composites for ballistic energy dissipation in trauma pack - Mazlan, Mazliah (2023)
The requirement to lessen the blunt trauma of the shield's back against body armour wearers prompted the quest for novel materials with excellent energy dissipation, flexibility, and affordability. This study developed a natural rubber-modified starch (NRS) composite as a residual impact energy absorber in a ballistic trauma pack. NRS composite is made using a melt compounding method with an internal mixer. The typical ingredients were 100 parts per hundred (phr) of natural rubber (NR), various loadings of tapioca starch (TS) and filler materials, curing agents and additives. The NRS composites were vulcanized in a hot press at 160 °C. In Stage 1, the effect of tapioca starch loadings (0, 5, 10, 20, 40, 60 phr) on mechanical properties and cure characteristics were analysed. The NRS vulcanizate with 20 phr TS was selected for its maximum mechanical properties and processability. In Stage 2, Response Surface Methodology (RSM) was used to optimize the other formulation parameters with the help of Design Expert 6.0.10 software. Four formulation variables, 1) type of fillers (carbon black (CB) and ZrO2 nanoparticles), 2) glycerol and 3) silane coupling agent (3-aminopropyltriethoxysilane) were evaluated for their rebound resilience, tensile strength, and cure characteristics. The regression models for the responses were chosen by comparing the observational data with the software's predicted values. A result of R2 close to unity from the analysis of variance indicates the model accuracy in representing the actual system. The samples were subjected to the Rheometer test, tensile test, hardness test, rebound resilience (RR) test, swelling test, compositional analysis using infrared Fourier transformation spectroscopy, morphological analysis via a Field Emission Scanning Electron Microscopy (FESEM), and Dynamic Mechanical Thermal Analysis (DMTA). Compared to vulcanizate without filler, TS at 20 phr showed the best compatibility with NR matrices due to enhanced cure characteristics, tensile energy absorption, hardness, and crosslink density. In Stage 3, the composites with the lowest RR (100 phr CB) and highest RR (50 phr CB) were chosen for the ballistic trauma test and tested against the effect of no. of layers (3 layers and 6 layers) and with (NRS composites) or without TS (NR composites). Using the Prototypa Universal Test Gun, NRS composites were subjected to the NIJ 0101.04 Level II Ballistic Resistance Test against 9 x 19 mm Full Metal Jacketed Round Nose (FMJ RN) bullet penetration. NR composites were integrated with mild steel plates to determine ballistic limit and back-face signature (BFS). Deformation patterns of the NR composites were observed and supported with morphological characteristics using FESEM to establish the failure mechanism. NRS composites manifested BFS of 4.55 (NRS-CB50) to 14.52 (NRS-CB100) for the range of energy dissipation between 507.00 to 562.50 J. NRS-CB50 with low RR value has depicted the highest potential to be used in trauma pack due to the enormous trauma reduction compared to the NRS-CB100 with high RR value. The presence of TS particles resulted in substantial chain mobility and improved the overall energy dissipation via viscous and elastic responses. The morphological characteristics of the deformed composite back face were in line with the BFS and energy adsorption of the composite under ballistic impact. The best NRS formulation and no. of layer for the trauma pack was selected to be at 100phr NR, 20phr TS, 50phr CB, 5phr glycerol and 6 layers.